Linguo-Stylistic Means in Patrick Suskind’s Novel “Perfume” - Navasardyan, Navasardyan (Bulletin of Yerevan University B: Philology, 2022)
The purpose of the article is to study the linguistic and stylistic devices of the novel by the German prose writer and playwright Patrick Suskind "Perfume", their features, as well as speech structures characteristic of different eras. In the course of the study analytical and comparative methods have been applied. The novel “Perfume” got well-known not only due to originality of plot and structure of its narration, in the base of which lies the interlacement of the postmodernist and existentialist novels’ principles, but also by the presence of varied linguo-stylistic means carrying out in the novel most different functions. Taking as a structural-semantic base for his novel the metaphor “smell”, as a conceptual unit, P.Suskind creates his authorial neologisms, formed by synaesthesical combining practically of all sense organs of a man. With the help of such a “matrix” the author succeeded to “compose” the image of the main character – Grenouille, as well as of other characters of the novel. Playing up the linguistic styles of the characters not only with the help of dialogs, but also of their inner “monologues”, the author realizes at the same time several functional tasks: the substantiation of their deeds, the bringing to light the pivotal essence of novel’s intrigue, shocking the reader by means of contrasting opposition of beauty and evil deed. The main task of the novel is the awareness of one's own status, the drama of one's own position, the tragedy in the world he created.
Keywords: Synesthesia; neologism; aroma; sense of smell; smell; combination of senses; olfactory genius